A method for flight test subject allocation on multiple test aircrafts based on improved genetic algorithm - Liu, Yibo; Xiao, Gang; Wang, Miao; Li, Tao (Aerospace systems (Online), 2019)
The civil aircraft flight test technology is complex and related to many systems. The efficiency and rationality of the flight test task planning has become one of the key factors affecting the flight test duration and cost. In the initial planning process of the flight test task, the allocation of a large amount of flight test subjects on multiple test aircrafts is a key issue. There are many shortcomings in manual planning based on work experience. However, the information about the existence of related automated assist algorithms or tools has not been found in the public information. Through the research on the workflow of the current civil flight test and the communication with the relevant departments, the main influencing factors and constraints related to the allocation of flight test subjects were summarized in this paper. The allocation process was simplified, and the core mathematical problem extracted and modeled. A method based on improved genetic algorithm to generate the flight test subject allocation scheme was designed. The superiority of the algorithm was proven by comparing with the research results of related reference literature. The case simulation of several engineering practical application scenarios was carried out, which demonstrated the prospect of this method being put into practical engineering applications.